Creativity in Motion: Examining the Creative Potential System and Enriched Movement Activities as a Way to Ignite It - Richard, Veronique; Holder, Darren; Cairney, John (Frontiers in Psychology, 2021)
In a global and highly competitive world, the importance of creativity is increasing as it supports adaptability, health, and actualization. Yet, because most research focuses on what it takes to produce creative artefacts, interventions supporting growth in creative potential remains underexplored. To address this limitation, the first goal of this paper is to review the creativity science literature to identify the elements that underpin the realization of an individual’s creative potential. The summary of the literature is presented using a framework which highlights the interactions between environmental elements (i.e., cultural values, social interactions, and material world) and actors’ elements (i.e., affective attributes and states, cognitive skills, and physical expression). Using a systemic perspective, the framework illustrates ‘what’ creativity enhancement interventions should aim for, to facilitate the emergence of creative actions. Given the current lack of holistic, embodied, and interactive evidence-based interventions to nurture the creative potential elements identified, the second part of this review builds on movement sciences literature and physical literacy conceptualisation to suggest that enriched movement activities are promising avenues to explore. Specifically, following nonlinear pedagogy approaches, an intervention called movement improvisation is introduced. Ecological dynamics principles are used to explain how improvising with movement in a risk-friendly environment can lead to cognitive, affective, social, and cultural repertoire expansion. To interrogate this argument further, the review concludes with possible solutions to withstand research challenges and raises future study questions. Overall, combining creativity and movement sciences in this review demonstrates the potential for well-designed movement interventions to ignite creative potential for individuals and overcome the tendency to remain anchored in a state of inertia.